Does Sex Affect Anticoagulant Use for Stroke Prevention in Nonvalvular Atrial Fibrillation?: The Prospective Global Anticoagulant Registry in the FIELD-Atrial Fibrillation. (March 2015) - Lip, Gregory Y.H.; Rushton-Smith, Sophie K.; Goldhaber, Samuel Z.; Fitzmaurice, David A.; Mantovani, Lorenzo G.; Goto, Shinya; Haas, Sylvia; Bassand, Jean-Pierre; Camm, Alan John; Ambrosio, Giuseppe; Janský, Petr; Al Mahmeed, Wael; et al.
Abstract : Background—: Among patients with atrial fibrillation (AF), women are at higher risk of stroke than men. Using prospective cohort data from a large global population of patients with nonvalvular AF, we sought to identify any differences in the use of anticoagulants for stroke prevention in women and men. Methods and Results—: This was a prospective multicenter observational registry with 858 randomly selected sites in 30 countries. A total of 17 184 patients with newly diagnosed (⩽6 weeks) nonvalvular AF and ≥1 additional investigator-defined stroke risk factor(s) were recruited (March 2010 to June 2013). The main outcome measure was the use of anticoagulants (vitamin K antagonists, factor Xa inhibitors, and direct thrombin inhibitors) for stroke prevention at AF diagnosis. Of 17 184 patients enrolled, 43.8% were women. More women than men were at moderate-to-high risk of stroke (CHADS2 score ≥2: 65.1% versus 54.7%). Rates of anticoagulant use were not different overall (60.9% of men versus 60.8% of women) and in patients with a CHADS2 score ≥2 (adjusted odds ratio for women versus men, 1.00; 95% confidence interval, 0.92–1.09). In patients at low risk (CHA2 DS2 -VASc of 0 in men and 1 in women), 41.8% of men and 41.1% of women received an anticoagulant. In patients at high risk (CHA2 DS2 -VASc score ≥2), 35.4% of men and 38.4% of women did not receive an anticoagulant. Conclusions—: These contemporary global data show that anticoagulant use for stroke prevention is no different in men and women with nonvalvular AF. Thromboprophylaxis was, however, suboptimal in substantial proportions of men and women, with underuse in those at moderate-to-high risk of stroke and overuse in those at low risk. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01090362. Abstract : Supplemental Digital Content is available in the text.